2020
DOI: 10.5194/acp-20-13455-2020
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of the surface ozone and fine particulate matter to meteorological parameters in China

Abstract: Abstract. Meteorological conditions play important roles in the formation of ozone (O3) and fine particulate matter (PM2.5). China has been suffering from serious regional air pollution problems, characterized by high concentrations of surface O3 and PM2.5. In this study, the Community Multiscale Air Quality (CMAQ) model was used to quantify the sensitivity of surface O3 and PM2.5 to key meteorological parameters in different regions of China. Six meteorological parameters were perturbed to create different me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 42 publications
2
21
0
1
Order By: Relevance
“…Among all of the pollutants, the deweathered Zn, Cr, Fe, Pb, and Ca experienced decrease rates of more than 50 % due to the lockdown measures. It was well known that Zn, Cr, and Fe originated mainly from the metallurgical industry (Sun et al, 2018;Zhu et al, 2018), while Pb might be derived from coal-fired power plants (Cui et al, 2019;Meng et al, 2020). During the COVID-19 outbreak, most of the industries have been shut down, and energy production by coal-fired power plants was reduced by one-third (Chang et al, 2020).…”
Section: The Impact Of Emission Reduction In Air Qualitymentioning
confidence: 99%
“…Among all of the pollutants, the deweathered Zn, Cr, Fe, Pb, and Ca experienced decrease rates of more than 50 % due to the lockdown measures. It was well known that Zn, Cr, and Fe originated mainly from the metallurgical industry (Sun et al, 2018;Zhu et al, 2018), while Pb might be derived from coal-fired power plants (Cui et al, 2019;Meng et al, 2020). During the COVID-19 outbreak, most of the industries have been shut down, and energy production by coal-fired power plants was reduced by one-third (Chang et al, 2020).…”
Section: The Impact Of Emission Reduction In Air Qualitymentioning
confidence: 99%
“… 11 14 A recent study suggested that PM 2.5 in China is sensitive to a few key meteorological parameters, such as wind speed, planetary boundary layer height (PBLH), temperature, and relative humidity (RH), while O 3 is mainly sensitive to temperature. 15 Therefore, variations in meteorological conditions before and during the lockdown could contribute to the changes in PM 2.5 and O 3 concentrations. However, it remains unclear about the respective impacts of emission reduction and meteorological conditions on air quality during the lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, summer typhoon activities might have weakened the WPSH intensity over the YRD region, leading to the eastward retreat and northward shift of the WPSH. As a result, the high WS across coastal areas was able to ease the ground-level O 3 pollution (Shu et al, 2016). For the BTH and PRD regions, the high PF tended to suppress the production of O 3 .…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, there were 167, 117, 52 and 32 d for Type 1, Type 2, Type 3 and Type 4 over the study period, respectively. Since the WPSH's movement is generally affected by the weather phenomena of its surrounding climatic systems (such as typhoons and the Tibetan high) (Ge et al, 2019;Liu and You, 2020;Shu et al, 2016;Wang et al, 2019), it may have resulted in a shortterm southward retreat during the advancement of the WPSH (e.g., around 10 August 2018) and a short-term northward advancement during its process of retreat (e.g., 21 and 29 August 2016). For instance, tropical storm NEPARTAK generated at 00:00 UTC (08:00 BJT) 3 July 2016 over the western North Pacific and upgraded to a super typhoon at 12:00 UTC (20:00 BJT) 5 July 2016 (Fig.…”
Section: Objective Classification Of Large-scale Swps In Summermentioning
confidence: 99%
See 1 more Smart Citation